Characteristics of immersive citizen science experiences that drive conservation engagement. Issue 4 (17th May 2022) - Day, Georgia; Fuller, Richard A.; Nichols, Cassandra; Dean, Angela J.
Abstract: The biodiversity crisis poses a real and present global threat to humanity. The acceleration of species and ecosystem decline coupled with climate change suggests that as it stands, nature cannot absorb the pressure humanity is placing on the planet. Bold new approaches to biodiversity conservation are needed. Promoting an engaged community is an important part of achieving conservation outcomes. Research shows that citizen science has the potential to elicit conservation engagement. However, research has not specifically explored how intensive citizen science expedition programs contribute to change. Here we use transformative learning theory as a tool to investigate how participation in citizen science programs influences conservation engagement. We analysed evaluation surveys of Earthwatch Institute citizen science participants ( N = 608) and conducted in‐depth interviews ( N = 11), to examine the links between citizen science experiences and engagement outcomes. We discovered that while nature‐based components of citizen science programs attract participants and create a salient environment for transformation, these are not objectively associated with engagement outcomes. Strengthened awareness was associated with learning, social interactions and cultural experiences, whereas intentions to engage in conservation action was only influenced by experiencing a sense of contribution. Rather than focusing only on learning and nature experiences, our results suggest that the elements of citizen science programs which support social change may require allowing participants to develop a sense of contribution amid an interactive social environment. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.